Improving Elementary School Students' Science Literacy Abilities in Augment Reality-Based Science Learning - Auralia, Annisa; Juliani, Dinda Aghisna (Universitas Pendidikan Ganesha, 2024)
Scientific literacy plays an important role in the success of education, especially in science learning. However, in reality, mastery of scientific literacy is inversely proportional to the current reality of science learning. The impact on the learning process is that students have difficulty understanding the material provided by the teacher. The aim of this research is to improve the scientific literacy skills of elementary school students through the use of Augmented Reality-based technology in science learning.The research method used is a quasi-experimental method, where data collection uses observation and tests. The research sample consisted of 35 fifth grade student in one of elementary schools in the city of Cirebon who were randomly selected and divided into an experimental group and a control group. Data analysis uses descriptive and inferential statistical techniques. The research results showed that students in the experimental group experienced a significant increase in post-test scores compared to the control group and that the integration of Augment Reality in science learning was effective in increasing the scientific literacy of elementary school students. The implications of this research are efforts to provide education to help elementary school students to be more involved in the learning process and strengthen their understanding of scientific concepts. This can have a positive impact on improving students' scientific literacy abilities.